2017
DOI: 10.1097/mlr.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

“Where’s My Choice?” An Examination of Veteran and Provider Experiences With Hepatitis C Treatment Through the Veteran Affairs Choice Program

Abstract: The Choice Program has the potential to increase veteran access to HCV treatment, but veterans and VA providers have described substantial problems in the initial years of the program. Enhancing care coordination, incorporating shared decision-making, and establishing a wide network of community providers may be important areas for further development in designing community-based specialist services for needy veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…In particular, increased fragmentation of care may result in additional challenges for coordination and continuity of care provided . The impact of increased care fragmentation is expected to be more pronounced for Veterans with greater health care utilization, and among them women Veterans, who have additional health burdens and complex care needs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, increased fragmentation of care may result in additional challenges for coordination and continuity of care provided . The impact of increased care fragmentation is expected to be more pronounced for Veterans with greater health care utilization, and among them women Veterans, who have additional health burdens and complex care needs …”
Section: Introductionmentioning
confidence: 99%
“…3 The impact of increased care fragmentation is expected to be more pronounced for Veterans with greater health care utilization, and among them women Veterans, who have additional health burdens and complex care needs. 4,5 Women Veterans (WVs) constitute the fastest growing segment of VA patients, but represent a numerical minority within VA facilities (<10 percent of VA users). 6 Delivering women's health (WH) services, maintaining provider competencies in WH, and providing gender-sensitive care environments have been challenging for VA facilities traditionally oriented toward the care of male patients.…”
Section: Introductionmentioning
confidence: 99%
“…We identified five studies examining P4P or related implementation factors in Veteran populations in community settings. [37][38][39][40][41] One study identified published survey instruments examining cross-system access and coordination. 37 Across studies, findings suggest that Veterans, providers, and VHA administrators are concerned that VCP already has and will continue to result in fragmented care, poor communication and coordination among providers, and places an additional burden on and VHA providers and on Veterans.…”
Section: P4p At the Intersection Of Vha And Community Carementioning
confidence: 99%
“…37 Across studies, findings suggest that Veterans, providers, and VHA administrators are concerned that VCP already has and will continue to result in fragmented care, poor communication and coordination among providers, and places an additional burden on and VHA providers and on Veterans. 37,40,41 Other concerns include barriers to sharing medical records, [39][40][41] and differences between providers who are interested in VCP participation and those who are not (see online Appendix 12 for detail). 38 Findings from Key Informant Interviews (See Figure 5 for Themes, and Table 3 for Quotes).…”
Section: P4p At the Intersection Of Vha And Community Carementioning
confidence: 99%
“…Substance use as well as medical comorbidity has also been associated with a lower likelihood of a veteran receiving a prescription for the new DAA medication (Lin et al, ). Additionally, structural factors, such as fragmentation of care and billing issues may affect access to treatment (Tsai et al, ). However, these findings do not represent the full spectrum of challenges faced by veterans with HCV as they make the choice to undergo treatment.…”
Section: Introductionmentioning
confidence: 99%